Reciprocal effect of parental lines on the physiological potential and seed composition of corn hybrid seeds - Santos, Juliana F. [UNESP]; Dirk, Lynnette M.A.; Bruce Downie, A.; Sanches, Mauricio F.G. [UNESP]; Vieira, Roberval D. [UNESP] (Cambridge University Press (CUP), 2017)
Obtaining corn hybrid seeds (Zea mays L.) with high vigour depends on the parental lines and the direction of the cross, and this relates to seed desiccation tolerance and composition. This research studied reciprocal crosses between pairs of proprietary, elite parent lines (L1 and L5; L2 and L4) producing hybrid seeds with different qualities attempting to correlate vigour with seed composition, focusing on storage proteins, starch and soluble sugar amounts. Four corn hybrid seed lots produced from reciprocal crosses were compared (HS 15 with HS 51, and HS 24 with HS 42) by assessing germination, vigour, and seedling emergence in the field. Seed composition was assessed in mature, dehydrated seeds. Proteins were extracted, quantified, and analysed by electrophoresis and densitometry. Starch amounts were assessed using a kit and soluble sugars were determined using high performance liquid chromatography with pulsed electrochemical detection. The L1 and L2 lineages, used as female parents, provided seeds with lower vigour; however, the quantification of major protein bands, and sucrose, raffinose and stachyose were similar between seed lot pairs. While both total seed protein and starch varied between reciprocal hybrids for one of the two sets of crosses, the amounts of neither correlated with seed vigour. Interestingly, hybrids with low seed vigour (HS 15, HS 24) accumulated greater amounts of fructose relative to their reciprocal; correlation analysis confirmed these results. We demonstrate different effects on seed vigour dependent on the maternal parent in reciprocal crosses producing hybrid corn seeds. We also show that vigour is negatively correlated with seed reducing sugar contents.
Keywords: parental effects; raffinose; vigour; Zea mays (L.)